Sensitivity of the Antarctic ice sheets to the warming of marine isotope substage 11c - Mas e Braga, Martim; Bernales, Jorge; Prange, Matthias; Stroeven, Arjen; Rogozhina, Irina (The Cryosphere, 2023)
Funding: This research has been supported by the Swedish Research Council (grant no. 2016-04422), the German Research Foundation (grant no. 1158-365737614), the US National Science Foundation (grant no. PLR-1542930), and the Norwegian Polar Institute/NARE (grant no. 2015/38/7/NK/ihs). Jorge Bernales has been supported by the MAGIC-DML project through DFG SPP 1158 (RO 4262/1-6). The article processing charges for this open-access publication were covered by Stockholm University. Studying the response of the Antarctic ice sheets during periods when climate conditions were similar to the present can provide important insights into current observed changes and help identify natural drivers of ice sheet retreat. In this context, the marine isotope substage 11c (MIS11c) interglacial offers a suitable scenario, given that during its later portion orbital parameters were close to our current interglacial. Ice core data indicate that warmer-than-present temperatures lasted for longer than during other interglacials. However, the response of the Antarctic ice sheets and their contribution to sea level rise remain unclear. We explore the dynamics of the Antarctic ice sheets during this period using a numerical ice sheet model forced by MIS11c climate conditions derived from climate model outputs scaled by three glaciological and one sedimentary proxy records of ice volume. Our results indicate that the East and West Antarctic ice sheets contributed 4.0–8.2 m to the MIS11c sea level rise. In the case of a West Antarctic Ice Sheet collapse, which is the most probable scenario according to far-field sea level reconstructions, the range is reduced to 6.7–8.2 m independently of the choices of external sea level forcing and millennial-scale climate variability. Within this latter range, the main source of uncertainty arises from the sensitivity of the East Antarctic Ice Sheet to a choice of initial ice sheet configuration. We found that the warmer regional climate signal captured by Antarctic ice cores during peak MIS11c is ...